MODEL PENGUKURAN KINERJA KARYAWAN BERDASARKAN KOMITMEN, MOTIVASI KERJA DAN GAYA KEPEMIMPINAN - Basuki, Rahmat; Setyawan, Anton Agus; Wajdi, M Farid (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2017)
This study aims to measure the effect of leadership styles, organizational commitment to performance with the mediation of motivation in the civil service of the Faculty of Universities in Surakarta. The study population was a civil servant employees in the faculty. The sample is determined by the saturated sample technique, the entire employee staff respondents as many as 76 people. Methods of data collection techniques used are questionnaire. Data analysis method used is the method of path analysis (path analysis). From the results of this study concluded that the style of leadership, organizational commitment and motivation of jointly have a significant influence on employee performance. While the results of the t test of leadership style variable result that leadership style has no effect on the motivation and performance of the organization's commitment and motivation.Variabel partially have a significant influence on employee performance. With the result that the path analysis variables mediate motivational leadership style on employee performance. Motivation also mediate organizational commitment to employee performance. Judging from the coefficient (R Square) we can conclude that the motivation was influenced variable leadership style and organizational commitment of 0.46% while the rest influenced by other factors beyond the study variables. Performance is influenced by the motivation of employees by 44% and the rest influenced by other factors beyond the variables. Performance of employees affected by variables of leadership style and organizational commitment by 36% while 64% is variable - the other variables outside the study.